Preparation method and application of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with sandwich structure
By preparing polychlorinated styrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage all-organic composite films with sandwich structure, the problem of low energy storage density of existing polymer films is solved, and high dielectric performance and energy storage performance are improved, and it is suitable for high-power electronic equipment and new energy vehicles.
Patent Information
- Application Number
- CN202411500823.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing polymer film has low energy storage density, which limits its application in high-power electronic equipment, new energy vehicles and grid storage systems.
The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage all-organic composite film with a sandwich structure is used to prepare by electrospinning to adjust the pore structure and physical and chemical characteristics of the film to improve the energy storage performance.
It significantly improves the dielectric performance and energy storage performance of the film, reduces losses, and is suitable for electrical, electronic and new energy vehicles.
Smart Images

Figure CN119177518B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of all-organic polymer insulation, and in particular to a preparation method and application of a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure. Background Art
[0002] Under the strategic goals of innovation-driven development, high-quality development, and green and low-carbon transformation, as well as the strategic requirements of high-quality development, industrial upgrading and product quality improvement are important directions. Dielectric capacitors are core components in many high-end electronic products. Their performance directly determines the efficiency, reliability and stability of the equipment, and plays an important role in promoting the country's high-quality development.
[0003] Dielectric capacitors with solid dielectric materials as dielectric layers have ultra-high power density and are widely used in high-power electronic devices, new energy vehicles, and power grid storage systems. Compared with inorganic dielectric capacitors, polymer-based dielectric capacitors are favored due to their high breakdown field strength, low dielectric loss, and strong processability, providing a wider space for the microstructure design and macro performance regulation of film capacitors and embedded capacitors. However, the energy storage density of pure polymer dielectrics is generally low, which greatly limits its practical application and further development. For example, the most typical representative of commercial dielectric capacitors, biaxially oriented polypropylene (BOPP), has an energy storage density of only 2-3J / cm 3 Capacitors made of single organic dielectric materials have limited the development of dielectric film capacitors towards miniaturization / intelligence. Therefore, the exploration and research of composite organic materials with higher energy storage density is of great significance.
[0004] According to the average dipole moment value of the polymer matrix molecules of polymer dielectrics, polymers can be divided into non-polar polymers and polar polymers. Typical non-polar dielectric polymers include polyethylene (PE), polytetrafluoroethylene (PTFE) and polypropylene (PP). In view of the low dielectric properties and energy storage performance of non-polar dielectric polymers, researchers have focused on polar polymer materials with high dielectric constants and energy storage densities, including polyimide (PI), polyvinyl chloride (PVC), polyurethane (PU) and polytetrafluoroethylene (PTFE). The study of ferroelectric polymers is one of the hot topics, among which polyvinylidene fluoride (PVDF) has the potential to become a new type of high energy storage polymer film due to its strong polarity and high dielectric constant (8-12). However, the ferroelectricity of PVDF leads to energy loss, high dielectric loss, hysteresis effect and residual polarization. These characteristics make PVDF have obvious energy loss during the charge and discharge cycle, thereby reducing the overall energy storage efficiency. Poly(vinylidene fluoride-co-hexafluoropropylene) (P(VDF-HFP)) is a fluorinated polymer obtained by copolymerizing PVDF with hexafluoropropylene (HFP). Not only does it retain a high dielectric constant, but by introducing HFP units, it destroys the high crystallinity and β-phase crystal structure of PVDF and reduces its ferroelectricity. At the same time, it reduces the charge retention effect in the material, reduces losses, and improves the efficiency of energy storage devices.
[0005] Research on the influence of the macrostructure of composite dielectrics on their performance is also one of the hot topics in recent years, mainly including single-layer structure, sandwich structure, multi-layer structure, concentration gradient structure, etc. The core idea of the sandwich structure is to insert an insulating layer with high breakdown strength between two highly polarized layers, which prevents the development of the breakdown path of the polarized layer, resulting in the material obtaining a high breakdown strength. Compared with the multilayer structure and the concentration gradient structure, it has fewer interface and interlayer defects, which helps to reduce dielectric loss and charge leakage. At the same time, electric field optimization is easier to optimize and control through design and experiment, avoiding local excessive electric field concentration and reducing the risk of breakdown. Among the existing polymer film preparation technologies, spin coating, hot pressing, electrospinning and solution casting are the four commonly used methods. The spin coating method mainly relies on centrifugal force to spin-coat the polymer solution on the substrate to form a film, and the film thickness is thin and the distribution uniformity is poor. The hot pressing method is to heat the polymer raw material to above the melting point, and the polymer solution expands along the mold direction under pressure to prepare a polymer film. It requires many processes and the heating, pressure-maintaining and cooling process takes a long time. The electrospinning method is to extrude the polymer solution evenly from the needle at the top of the syringe under the action of an electric field. The material is in the form of fibers, but it needs to be combined with other processes to prepare a dense structure polymer film. The solution casting method is to evenly coat the polymer solution on the substrate and form a film after the solvent evaporates. For films with higher precision or special functions, it may be necessary to combine other technologies such as PVD, CVD, etc. for further optimization. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems and to provide a preparation method and application of a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure.
[0007] A method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure is carried out according to the following steps:
[0008] Step S1: preparing a polychlorostyrene mixed solution;
[0009] After heating and stirring the p-chlorostyrene solution, adding the benzoyl peroxide solution, mixing evenly and cooling to obtain a polychlorostyrene mixed solution a;
[0010] Step S2: preparing a poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution;
[0011] Adding poly(vinylidene fluoride-co-hexafluoropropylene) particles into N,N-dimethylacetamide solution, performing ultrasonic dispersion and magnetic stirring at a temperature of 60 to 70° C., and then evacuating to obtain poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b;
[0012] Step S3: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution;
[0013] The polychlorostyrene mixed solution a obtained in step S1 is added to the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2, and ultrasonically dispersed and magnetically stirred at a temperature of 60 to 70° C., and then vacuumed to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c;
[0014] Step S4: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film having a sandwich structure;
[0015] The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c obtained in step S3 and the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2 are sequentially prepared according to the steps of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c, poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b and polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c. The method comprises the following steps: electrospinning is performed at a volume ratio of 1:1:1 to obtain a wet film d; the wet film d is dried, hot-pressed, and finally cooled to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) / poly(vinylidene fluoride-co-hexafluoropropylene) / polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite film, wherein the mass fraction of polychlorostyrene in the outer film polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) of the composite film is 1%, 3% or 5%.
[0016] An application of a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure, and the application of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure in the fields of electrical, electronic and new energy vehicles.
[0017] Beneficial effects of the present invention:
[0018] (1) The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure of the present invention is prepared by electrospinning. Polyvinylidene fluoride (PVDF) is a commonly used piezoelectric material that can induce the accumulation of charges through an electric field. At the same time, the introduction of polychlorostyrene provides better mechanical strength and flexibility, and adjusts the pore structure of the film, so that it increases the storage of charges on a larger surface area and improves the energy storage performance.
[0019] (2) The present invention can precisely control the physical and chemical properties of the composite film by adjusting the ratio of polychlorostyrene in PVDF, spinning parameters and the structure of the film, so that it can meet the requirements under different conditions, such as high temperature and high pressure.
[0020] (3) The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure prepared by the method of the present invention has excellent dielectric properties and energy storage properties, and reduced losses, and can be widely used in advanced fields such as electrical, electronic and new energy vehicles.
[0021] (4) The preparation process of the present invention is simple, economical and practical, and effectively saves resources, thus providing a good strategy for developing new application pathways for all-organic composite media.
[0022] The invention can obtain a preparation method and application of a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A scanning electron microscope image of a pure poly(vinylidene fluoride-co-hexafluoropropylene) film prepared in Example 4 after electrospinning and drying;
[0024] Figure 2 The present invention shows that the outer layer polychlorostyrene-poly (vinylidene fluoride-co-hexafluoropropylene) film uses a polychlorostyrene-poly (vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with different mass fractions of polychlorostyrene at 500-4000cm -1 Fourier transform infrared spectra within the wavelength range, a represents pure poly(vinylidene fluoride-co-hexafluoropropylene) film, b represents polychlorostyrene with a mass fraction of 1%, c represents polychlorostyrene with a mass fraction of 3%, and d represents polychlorostyrene with a mass fraction of 5%;
[0025] Figure 3 A graph showing the dielectric constant test results of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with different mass fractions of polychlorostyrene in the outer layer polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) film of the present invention, wherein ■ represents a pure poly(vinylidene fluoride-co-hexafluoropropylene) film, ● represents a mass fraction of 1% of polychlorostyrene, ▲ represents a mass fraction of 3% of polychlorostyrene, and ▼ represents a mass fraction of 5% of polychlorostyrene;
[0026] Figure 4 A graph showing the loss tangent value test results of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with different mass fractions of polychlorostyrene in the outer layer polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) film of the present invention, wherein ■ represents a pure poly(vinylidene fluoride-co-hexafluoropropylene) film, ● represents a mass fraction of 1% of polychlorostyrene, ▲ represents a mass fraction of 3% of polychlorostyrene, and ▼ represents a mass fraction of 5% of polychlorostyrene;
[0027] Figure 5A discharge energy density diagram of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with different mass fractions of polychlorostyrene in the outer layer polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) film of the present invention, ■ represents a pure poly(vinylidene fluoride-co-hexafluoropropylene) film, ● represents a mass fraction of 1% for polychlorostyrene, ▲ represents a mass fraction of 3% for polychlorostyrene, and ▼ represents a mass fraction of 5% for polychlorostyrene. DETAILED DESCRIPTION
[0028] Specific implementation method 1: This implementation method is a method for preparing a polychlorostyrene-poly (vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure, which is carried out according to the following steps:
[0029] Step S1: preparing a polychlorostyrene mixed solution;
[0030] After heating and stirring the p-chlorostyrene solution, adding the benzoyl peroxide solution, mixing evenly and cooling to obtain a polychlorostyrene mixed solution a;
[0031] Step S2: preparing a poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution;
[0032] Adding poly(vinylidene fluoride-co-hexafluoropropylene) particles into N,N-dimethylacetamide solution, performing ultrasonic dispersion and magnetic stirring at a temperature of 60 to 70° C., and then evacuating to obtain poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b;
[0033] Step S3: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution;
[0034] The polychlorostyrene mixed solution a obtained in step S1 is added to the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2, and ultrasonically dispersed and magnetically stirred at a temperature of 60 to 70° C., and then vacuumed to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c;
[0035] Step S4: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film having a sandwich structure;
[0036] The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c obtained in step S3 and the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2 are sequentially prepared according to the steps of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c, poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b and polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c. The method comprises the following steps: electrospinning is performed at a volume ratio of 1:1:1 to obtain a wet film d; the wet film d is dried, hot-pressed, and finally cooled to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) / poly(vinylidene fluoride-co-hexafluoropropylene) / polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite film, wherein the mass fraction of polychlorostyrene in the outer film polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) of the composite film is 1%, 3% or 5%.
[0037] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that in step S1, the para-chlorostyrene solution is heated to 60-70°C in an oil bath, stirred at a stirring rate of 200-300 rpm for 1-2 hours, and then a benzoyl peroxide solution is added, and the mixture is mixed and stirred at a stirring rate of 200-300 rpm for 4-5 hours, and then naturally cooled to obtain a polychlorostyrene mixed solution a.
[0038] The other steps are the same as those in the first specific implementation.
[0039] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that the mass ratio of the p-chlorostyrene solution to the benzoyl peroxide solution in step S1 is (2.0-2.1) g: (0.02-0.03) g.
[0040] The other steps are the same as those in the first or second embodiment.
[0041] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that before adding the poly(vinylidene fluoride-co-hexafluoropropylene) particles to the N,N-dimethylacetamide solution in step S2, they are first dried under vacuum conditions at 60 to 70°C for 7 to 8 hours.
[0042] The other steps are the same as those in Specific Embodiments 1 to 3.
[0043] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the ratio of the mass of the poly(vinylidene fluoride-co-hexafluoropropylene) particles described in step S2 to the volume of the N,N-dimethylacetamide solution is (1.58-1.60) g: (5-6) mL.
[0044] The other steps are the same as those in Specific Embodiments 1 to 4.
[0045] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the ultrasonic dispersion time in step S2 and step S3 is 30 to 40 minutes, and the magnetic stirring time is 6 to 7 hours.
[0046] The other steps are the same as those in Specific Embodiments 1 to 5.
[0047] Specific embodiment seven: The difference between this embodiment and any one of specific embodiments one to six is: the process parameters of electrospinning in step S4: the humidity in the chamber of the electrospinning machine is 40-45RH%, +11kV-+12kV voltage is applied to the needle, -11kV--12kV voltage is applied to the high-speed orienting machine, and the needle advancement speed is 0.8mm / min-1.0mm / min; the wet film d described in step S4 is placed in a vacuum oven at 60-70℃ and dried for 11-12h.
[0048] The other steps are the same as those in Specific Embodiments 1 to 6.
[0049] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that: in step S4, the hot pressing treatment is carried out at a temperature of 210 to 220°C and a pressure of 12 to 15 MPa for 10 to 12 minutes; the cooling is carried out by circulating water cooling for 10 to 15 minutes.
[0050] The other steps are the same as those in Specific Embodiments 1 to 7.
[0051] Specific embodiment 9: The difference between this embodiment and any one of specific embodiments 1 to 8 is that the thickness of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) / poly(vinylidene fluoride-co-hexafluoropropylene) / polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite film described in step S4 is 14 to 19 μm.
[0052] The other steps are the same as those in Specific Embodiments 1 to 8.
[0053] Specific embodiment ten: This embodiment provides an application of a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure, and the application of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure in the fields of electrical, electronic and new energy vehicles.
[0054] The following examples are used to verify the beneficial effects of the present invention:
[0055] Example 1: A method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure, which is carried out according to the following steps:
[0056] Step S1: preparing a polychlorostyrene mixed solution;
[0057] 2.0 g of p-chlorostyrene solution was heated to 60° C. in an oil bath, stirred at a stirring rate of 260 rpm for 1 h, 0.02 g of benzoyl peroxide solution was added, and the mixture was stirred at a stirring rate of 260 rpm for 4 h, and then naturally cooled to obtain a polychlorostyrene mixed solution a;
[0058] Step S2: preparing a poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution;
[0059] First, poly(vinylidene fluoride-co-hexafluoropropylene) particles were dried under vacuum conditions at 60°C for 7 hours, and then 1.58 g of poly(vinylidene fluoride-co-hexafluoropropylene) particles and 5 mL of N,N-dimethylacetamide solution were added to a beaker, and ultrasonic dispersion was performed at a temperature of 60°C for 30 minutes, followed by magnetic stirring for 6 hours, and then vacuumization was performed to obtain poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b;
[0060] Step S3: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution;
[0061] 0.016 g of the polychlorostyrene mixed solution a obtained in step S1 was added to the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2, and ultrasonically dispersed for 30 min at a temperature of 60° C., and then magnetically stirred for 6 h, and then vacuumed to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c;
[0062] Step S4: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film having a sandwich structure;
[0063] The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c obtained in step S3 and the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2 are sequentially mixed according to 0.5 mL of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c, 0.5 mL of poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b and 0.5 mL of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c. Electrospinning to obtain a wet film d; drying the wet film d, hot pressing it at a temperature of 210° C. and a pressure of 15 MPa for 12 min, and finally cooling it with circulating water for 10 min to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) / poly(vinylidene fluoride-co-hexafluoropropylene) / polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite film, wherein the mass fraction of polychlorostyrene in the outer layer polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) of the composite film is 1%.
[0064] The process parameters of electrospinning in step S4 are as follows: the humidity in the chamber of the electrospinning machine is 40RH%, +11kV voltage is applied to the needle, -11kV voltage is applied to the high-speed orienting machine, and the needle advancement speed is 0.8mm / min; the wet film d described in step S4 is placed in a vacuum oven at 60°C and dried for 12h.
[0065] Example 2: In this example, the mass fraction of polychlorostyrene in the outer film is 3%. Other experimental conditions are the same as those in Example 1.
[0066] Example 3: In this example, the mass fraction of polychlorostyrene in the outer film is 5%. Other experimental conditions are the same as those in Example 1.
[0067] Example 4: In this example, only 1.5 mL of poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b was extracted for electrospinning to obtain a pure poly(vinylidene fluoride-co-hexafluoropropylene) film. Other experimental conditions were the same as those in Example 1.
[0068] Figure 1 The scanning electron microscope image of the pure poly (vinylidene fluoride-co-hexafluoropropylene) film prepared in Example 4 after electrospinning and drying; Figure 1 As shown, the spun membrane fibers have excellent morphology, fewer beaded structures, and more uniform thickness, resulting in a better fiber structure.
[0069] Figure 2The present invention shows that the outer layer polychlorostyrene-poly (vinylidene fluoride-co-hexafluoropropylene) film uses a polychlorostyrene-poly (vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with different mass fractions of polychlorostyrene at 500-4000cm -1 Fourier transform infrared spectra within the wavelength range, a represents pure poly(vinylidene fluoride-co-hexafluoropropylene) film, b represents polychlorostyrene with a mass fraction of 1%, c represents polychlorostyrene with a mass fraction of 3%, and d represents polychlorostyrene with a mass fraction of 5%.
[0070] like Figure 2 As shown in the FT-IR curve of pure poly(vinylidene fluoride-co-hexafluoropropylene) film, it can be seen that at the frequency of 531 cm -1 、876cm -1 and 1399cm -1 The absorption peaks correspond to the CF2 characteristic peaks of poly(vinylidene fluoride-co-hexafluoropropylene), which are respectively represented by bending vibration peak, asymmetric stretching peak and shear vibration peak. -1 、763cm -1 and 973cm -1 The α-phase characteristic absorption peak of the matrix is 531cm -1 、845cm -1 and 1067cm -1 The peak at 1066 cm corresponds to the characteristic absorption peak of the β phase of poly(vinylidene fluoride-co-hexafluoropropylene), which is the stretching vibration of CH2. -1 The absorption peak at 1145 cm is the characteristic vibration peak of CC skeleton. -1 The absorption peak at is the stretching vibration peak of CF. Comparing the FT-IR curves of pure film and composite film, the crystal form of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite films with different mass fractions of polychlorostyrene in the three outer films is the same as that of pure film, that is, there is no obvious effect on the crystal form of the matrix.
[0071] Figure 3 A graph showing the dielectric constant test results of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite films with different mass fractions of polychlorostyrene in the outer layer polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) film, ■ represents pure poly(vinylidene fluoride-co-hexafluoropropylene) film, ● represents 1% mass fraction of polychlorostyrene, ▲ represents 3% mass fraction of polychlorostyrene, and ▼ represents 5% mass fraction of polychlorostyrene.
[0072] like Figure 3 As shown, as the electric field frequency increases from 20 to 10 5As Hz increases, the dielectric constant of the composite film decreases. This is mainly because 3 -10 5 In the Hz frequency range, the dipoles in the composite film cannot keep up with the changes in the electric field, and their contribution gradually weakens, resulting in a decrease in the overall dielectric constant. 5 In the Hz frequency range, the dielectric constant of pure poly(vinylidene fluoride-co-hexafluoropropylene) film is lower than that of the composite film with a polychlorostyrene mass fraction of 3% in the outer film. At 1kHz, the dielectric constant of the pure film is 11.4, while the dielectric constant of the composite film with a polychlorostyrene mass fraction of 3% in the outer film is 11.5. This is because the chlorine atom in the C-Cl bond has a higher electronegativity than the carbon atom, which causes the C-Cl bond to present a certain polarization, that is, the chlorine atom attracts electron density, causing the electron cloud in the bond to shift toward the chlorine atom, thereby affecting the polarization and improving the dielectric constant of the composite film.
[0073] Figure 4 A graph showing the loss tangent test results of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage all-organic composite films with different mass fractions of polychlorostyrene in the outer layer of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) film, ■ represents pure poly(vinylidene fluoride-co-hexafluoropropylene) film, ● represents 1% mass fraction of polychlorostyrene, ▲ represents 3% mass fraction of polychlorostyrene, and ▼ represents 5% mass fraction of polychlorostyrene.
[0074] like Figure 4 As shown, as the electric field frequency increases from 20 to 10 5 When Hz increases, the loss tangent value of the composite film shows a trend of first decreasing and then increasing. When the test frequency is 1kHz, the dielectric loss of pure poly(vinylidene fluoride-co-hexafluoropropylene) film and composite film remains between 0.027-0.029. Among them, the dielectric loss of the composite film with a mass fraction of 3% polychlorostyrene in the outer film is lower than that of the pure poly(vinylidene fluoride-co-hexafluoropropylene) film. This is mainly due to the introduction of polychlorostyrene. The molecular structure of polychlorostyrene-Cl is relatively more stable, its polarity is relatively weak, and the internal polarization mechanism responds slowly, reducing the overall polarization loss. At the same time, due to the existence of the sandwich structure, the polychlorostyrene-Cl layer can inhibit the rapid polarization response of the dipoles and the migration of charges in the PVDF film to a certain extent, thereby reducing the dielectric loss of the film under high-frequency electric fields.
[0075] Figure 5A discharge energy density diagram of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with different mass fractions of polychlorostyrene in the outer layer polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) film, ■ represents pure poly(vinylidene fluoride-co-hexafluoropropylene) film, ● represents 1% mass fraction of polychlorostyrene, ▲ represents 3% mass fraction of polychlorostyrene, and ▼ represents 5% mass fraction of polychlorostyrene.
[0076] like Figure 5 As shown in the figure, when the mass fraction of polychlorostyrene in the outer film is 1%, 3% or 5%, the discharge energy density of the composite film is higher than that of the pure poly(vinylidene fluoride-co-hexafluoropropylene) film. When the electric field strength is 140MV / m, the discharge energy density of the pure poly(vinylidene fluoride-co-hexafluoropropylene) film is 0.79J / cm 3 The discharge energy density of the composite film with a polychlorostyrene mass fraction of 3% in the outer film is as high as 1.17 J / cm 3 , an increase of 48.1%. This is because the introduction of polychlorostyrene-Cl effectively reduces dielectric loss, and energy storage and release are more efficient. The interface effect formed by polychlorostyrene-Cl and PVDF in the sandwich structure plays an important role in enhancing energy storage capacity. The charge accumulation and polarization effect at the interface can effectively improve the overall electric field strength of the material. At the same time, the different electrical conductivities and polarities of polychlorostyrene-Cl and PVDF will also produce a certain interface polarization. This polarization effect can store more energy under high electric fields and release more energy during the discharge process, thereby increasing the discharge energy density.
Claims
1. A method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure, characterized in that The preparation method is carried out according to the following steps: Step S1: preparing a polychlorostyrene mixed solution; After heating and stirring the p-chlorostyrene solution, adding the benzoyl peroxide solution, mixing evenly and cooling to obtain a polychlorostyrene mixed solution a; Step S2: preparing a poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution; Adding poly(vinylidene fluoride-co-hexafluoropropylene) particles into N,N-dimethylacetamide solution, performing ultrasonic dispersion and magnetic stirring at a temperature of 60 to 70° C., and then evacuating to obtain poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b; Step S3: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution; The polychlorostyrene mixed solution a obtained in step S1 is added to the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2, and ultrasonically dispersed and magnetically stirred at a temperature of 60 to 70° C., and then vacuumed to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c; Step S4: preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film having a sandwich structure; The polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c obtained in step S3 and the poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b obtained in step S2 are sequentially prepared according to the steps of polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c, poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution b and polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) spinning precursor solution c. The method comprises the following steps: electrospinning is performed at a volume ratio of 1:1:1 to obtain a wet film d; the wet film d is dried, hot-pressed, and finally cooled to obtain a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) / poly(vinylidene fluoride-co-hexafluoropropylene) / polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite film, wherein the mass fraction of polychlorostyrene in the outer film polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) of the composite film is 1%, 3% or 5%.
2. The method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1, characterized in that In step S1, the para-chlorostyrene solution is heated in an oil bath to 60-70° C., stirred at a stirring rate of 200-300 rpm for 1-2 hours, and then a benzoyl peroxide solution is added, and the mixture is stirred at a stirring rate of 200-300 rpm for 4-5 hours, and then naturally cooled to obtain a polychlorostyrene mixed solution a.
3. A method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1 or 2, characterized in that The mass ratio of the p-chlorostyrene solution to the benzoyl peroxide solution in step S1 is (2.0-2.1) g: (0.02-0.03) g.
4. The method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1, characterized in that Step S2: Before adding the poly(vinylidene fluoride-co-hexafluoropropylene) particles into the N,N-dimethylacetamide solution, the particles are dried under vacuum at 60-70° C. for 7-8 hours.
5. A method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1 or 4, characterized in that The ratio of the mass of the poly(vinylidene fluoride-co-hexafluoropropylene) particles described in step S2 to the volume of the N,N-dimethylacetamide solution is (1.58-1.60) g: (5-6) mL.
6. The method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1, characterized in that The ultrasonic dispersion time in step S2 and step S3 is 30 to 40 minutes, and the magnetic stirring time is 6 to 7 hours.
7. The method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1, characterized in that The process parameters of electrospinning in step S4 are as follows: the humidity in the chamber of the electrospinning machine is 40-45 RH%, +11 kV-+12 kV voltage is applied to the needle, -11 kV--12 kV voltage is applied to the high-speed orienting machine, and the needle advancement speed is 0.8 mm / min-1.0 mm / min; the wet film d described in step S4 is placed in a vacuum oven at 60-70 ° C and dried for 11-12 hours.
8. The method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1, characterized in that In step S4, the hot pressing treatment is carried out at a temperature of 210 to 220° C. and a pressure of 12 to 15 MPa for 10 to 12 minutes; and the cooling is carried out by circulating water cooling for 10 to 15 minutes.
9. The method for preparing a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure according to claim 1, characterized in that The thickness of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) / poly(vinylidene fluoride-co-hexafluoropropylene) / polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) composite film described in step S4 is 14 to 19 μm.
10. Use of a polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure as claimed in any one of claims 1 to 9, characterized in that The application of the polychlorostyrene-poly(vinylidene fluoride-co-hexafluoropropylene) energy storage type all-organic composite film with a sandwich structure in the fields of electrical, electronic and new energy vehicles.
Citation Information
Patent Citations
Preparation method of P(VDF-HFP) (Poly(Vinyl Fluoride-Hexafluoropropylene)) inorganic compound porous nano fiber lithium ion battery separator
CN103258978A
All-organic composite material film and preparation method and application thereof
CN113121936A